A light microscopic and ultrastructural examination of calcified dental tissues of horses: 3. Dentine - Kilic, S.; Dixon, P.M.; Kempson, S.A. (British Equine Veterinary Association, 1997)
Ultrastructural examinations of equine dentine found that dentinal tubules extended from the amelodentinal junction towards the pulp forming primary curvatures. The number of dentinal tubules/unit area and their diameters increased significantly from the amelodentinal junction towards the pulp cavities, particularly in regular secondary dentine, but irregular secondary (tertiary) dentine contained no dentinal tubules. Dentinal tubules contained odontoblast processes that appeared to extend as far as the amelodentinal junction, but due to iatrogenic loss during specimen preparation, odontoblasts were seldom found in regular secondary dentine. In primary dentine, the dentinal tubules were surrounded by large amounts of peritubular dentine that increased in diameter from the amelodentinal junction towards the junction of primary and secondary dentine. The site of the dentinal tubule within the peritubular dentine varied at different dentinal sites. Peritubular dentine was present in primary dentine only and was surrounded by a thin layer of intertubular dentine. When acid etched, peritubular dentine gave dentine a honeycomb appearance adjacent to the junction of primary and secondary dentine.
Keywords: Calcified dental tissue; Dentine; Horse; Light and electron microscopy